Management of residues containing naturally occurring radioactive material from uranium production and other activities : Specific safety guide. (International Atomic Energy Agency, 2021)
"This Safety Guide provides recommendations on the establishment of an appropriate regulatory framework for the management of naturally occurring radioactive material (NORM) residues in an integrated manner and using a graded approach. It also elaborates on roles and responsibilities, options for management of NORM residues, long term safety of NORM residues, and exemption and clearance. The publication is targeted at regulatory bodies, operating organizations, technical support organizations and other parties who are interested and involved in management of NORM residues."--Publisher's description
"STI/PUB/1883"--Title page verso
"August 2021"--Title page verso
"IAEA safety standards for protecting people and the environment."--Cover
Keywords: Radiation, Background.; Radioactive substances.; Radioisotopes -- Safety measures.; Uranium.; Radioactive waste disposal.; elektronické knihy; electronic books